The Moderating Effects of Peer and Parental Support on the Relationship Between Vicarious Victimization and Substance Use - Fagan, Abigail A. (2014)
General strain theory (GST) hypothesizes that youth are more likely to engage in delinquency when they experience vicarious victimization, defined as knowing about or witnessing violence perpetrated against others, but that this relationship may be attenuated for those who receive social support from significant others. Based on prospective data from youth aged 8 to 17 participating in the Project on Human Development in Chicago Neighborhoods (PHDCN), this article found mixed support for these hypotheses. Controlling for prior involvement in delinquency, as well as other risk and protective factors, adolescents who reported more vicarious victimization had an increased likelihood of alcohol use in the short term, but not the long term, and victimization was not related to tobacco or marijuana use. Peer support did not moderate the relationship between vicarious victimization and substance use, but family support did. In contrast to strain theory’s predictions, the relationship between vicarious victimization and substance use was stronger for those who had higher compared with lower levels of family support. Implications of these findings for strain theory and future research are discussed